Growth of Samama, Jabon and Sengon Buto at Former Coal Mine Land PT. Tunas Inti Abadi, South Kalimantan. - Irdika Mansur; Rian Adiwicaksono (Jurnal Silvikultur Tropika, 2013)
Mined land reclamation is important in restoring environmental conditions back to conditions prior to mining activites. The purpose of this research is to observe the effect manure on samama (Anthocepalus macrophyllus), jabon (Anthocepalus cadamba) and sengon buto (Enterelobium cylocarpum) seedling growth on coal ex-mine site.. The research was conducted on mined site of PT. Tunas Inti Abadi, South Kalimantan. Experimental design used in this research was factorial in completely randomized design (CRD), with factors are spesies and dose of manure. Growth parameters measured were height and diameter growth of the seedlings. The results showed that the dose of manure significantly affected diameter growth, but did not significantly affect height growth of seedlings. Highest diameter growth was made by sengon buto. Spesies did not significantly affect diameter, but they showed significant differences on height growth rate. Sengon buto is the fastest growing species in term of height. Interaction between the dose of manure and species of plant affect only on diameter. The best species among the three spesies tested was sengon buto given 3 kg of manure per seedling.Keywords: Anthocepalus cadamba, Anthocepalus macrophyllus, Enterelobium cyclocarpum, mining, reclamation